1995
DOI: 10.1063/1.868693
|View full text |Cite
|
Sign up to set email alerts
|

Surface density function in premixed turbulent combustion modeling, similarities between probability density function and flame surface approaches

Abstract: Articles you may be interested inRelationships for maximum flame surface density and brush thickness through conditional analysis in turbulent premixed combustion Phys. Fluids 25, 075108 (2013); 10.1063/1.4816289Comparison of eddy dissipation model and presumed probability density function model for temperature prediction in a non-premixed turbulent methane flame AIP Conf.A dynamic flame surface density model for large eddy simulation of turbulent premixed combustion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(83 citation statements)
references
References 17 publications
2
81
0
Order By: Relevance
“…• Recent studies [35] [39] have shown that flame surface density and PDF approaches are related. In fact, E may be defined as the density of the iso-level c = c* surface, where c is the progress variable.…”
Section: Commentsmentioning
confidence: 96%
See 1 more Smart Citation
“…• Recent studies [35] [39] have shown that flame surface density and PDF approaches are related. In fact, E may be defined as the density of the iso-level c = c* surface, where c is the progress variable.…”
Section: Commentsmentioning
confidence: 96%
“…A summary and a comparison of various closure schemes for the E-equation (29) may be found in [14]. Recent developments are discussed in several papers [19] [38] [39] [41].…”
Section: Flame Surface Density Approachesmentioning
confidence: 99%
“…The presence of an exponential tails can be of particular importance in practical applications for combustion modeling [49][50][51][52]. has an intermittent nature, its PDF is very sensitive to the choice of the range for the horizontal axis.…”
Section: Probability Density Functionsmentioning
confidence: 99%
“…The FSD in Eq. (1) can be calculated directly from the DNS data using (Pope, 1988(Pope, , 1990Vervisch et al, 1995) …”
Section: Flame Surface Density and Flame Stretchmentioning
confidence: 99%
“…The contribution of nonpremixed part to the mixed mode combustion can be included using an appropriate combustion model as has been done in an earlier study (Domingo et al, 2002). One popular approach to model premixed part is the flame surface density (FSD) based modelling (Pope, 1988;Candel and Poinsot, 1990;Trouvé and Poinsot, 1994;Vervisch et al, 1995). The balance equation for the FSD, Σ, which is defined as the flame surface area per unit volume, is written as (Veynante and Vervisch, 2002)…”
Section: Introductionmentioning
confidence: 99%